2011
DOI: 10.1097/rlu.0b013e3182173823
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dual-Time-Point F-18 FDG PET/CT in the Assessment of Pleural Effusion in Patients With Non-Small-Cell Lung Cancer

Abstract: Dual-time-point F-18 FDG PET can improve the diagnostic accuracy in differentiating benign from malignant pleural disease, with high sensitivity and good specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 19 publications
1
29
0
Order By: Relevance
“…DP FDG-PET can improve the diagnostic accuracy in differentiating benign from malignant pleural disease and would help to avoid many unnecessary biopsies. In a retrospective study, including 61 NSCLC patients with pleural effusion, 48 all of them were submitted to total-body FDG-PET/CT imaging at 60 Ϯ 10 minutes after tracer injection, and 31 patients had second delayed imaging for the chest (at 90 Ϯ 10 minutes). In this series, the change in SUVs over time calculated with DP technique was helpful in differentiating malignant pleural disease from benign inflammatory process (sensitivity 100%, specificity 94%, and accuracy 97%).…”
Section: Lung Cancermentioning
confidence: 99%
“…DP FDG-PET can improve the diagnostic accuracy in differentiating benign from malignant pleural disease and would help to avoid many unnecessary biopsies. In a retrospective study, including 61 NSCLC patients with pleural effusion, 48 all of them were submitted to total-body FDG-PET/CT imaging at 60 Ϯ 10 minutes after tracer injection, and 31 patients had second delayed imaging for the chest (at 90 Ϯ 10 minutes). In this series, the change in SUVs over time calculated with DP technique was helpful in differentiating malignant pleural disease from benign inflammatory process (sensitivity 100%, specificity 94%, and accuracy 97%).…”
Section: Lung Cancermentioning
confidence: 99%
“…In these numerous studies, attempts have been made to qualify and quantify the impact of the length of the injection-to-scan time interval on differentiating malignant processes from benign processes. As one might expect, the findings reported amongst these various investigators have been highly variable, with some supporting the use of delayed phase and dual-time-point diagnostic 18 F-FDG PET imaging approaches [66-77,81-84,86,87,91-93,95-100,103-108,110,111,113,114,117-122,124-128,131,133,134,136,138,141,143,146,149,152,153,155,157,160-163,165,167,169], and with others not [65,78,89,90,94,101,102,109,115,116,123,129,130,132,135,137,139,140,147,148,150,151,156,158,164,166,168]. …”
Section: Discussionmentioning
confidence: 99%
“…81 As stated earlier, it has been reported that dualtime point 18 F-FDG-PET can provide better discrimination of benign and malignant lung nodules and pleural changes when compared with that using structural imaging. 72,82 Thus, FDG-PET might have some role in pneumoconiosis diagnostic or prognostic monitoring, but much more clinical evaluation is required.…”
Section: Nononcologic Applicationsmentioning
confidence: 99%